ANTIMICROBIAL AND ANTICANCER ACTIVITY OF SILVER NANOPARTICLES FROM EDIBLE MUSHROOM: A REVIEW - KC, Priyadarshni; PU, Mahalingam (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Biologically inspired nanoparticle synthesis is currently a rapid expanding area of research in nanotechnology. Nanoparticle synthesis utilizing the bioresources such as plants and microbes appears to be a viable, low-cost, and eco-friendly approach. Especially mushrooms can be used for largescale synthesis of silver nanoparticles as mushroom produces many proteins that reduce the silver nitrate during the biosynthesis. Silver nanoparticles can be characterized using ultraviolet-visible (UV-VIS) spectroscopy, fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, energy dispersive X-ray, and transmission electron microscope. Silver nanoparticles possess high antibacterial activity since silver in different forms has been extensively used as a medicine for curing diseases and promote wound healing. Silver nanoparticles have high surface specific area, which will lead to excellent antimicrobial activity as compared with bulk metallic silver. Further, the silver nanoparticles show anticancer activity against various cell lines such as human epidermoid larynx carcinoma (HEP-2), colon adenocarcinoma (HCT-116), breast adenocarcinoma (MCF-7), liver carcinoma (Hep-G2), and intestinal adenocarcinoma (Caco2) were well documented. This review intends to present green synthesis of silver nanoparticles and their application as antimicrobial and anticancer agents. Keywords: Silver nanoparticles, Bioresources, Mushroom, Antimicrobial activity, Anticancer property.